Women offenders who served community sentences: A view from Catalonia - Vasilescu, Cristina (European journal of probation, 2021)
Unlike in other jurisdictions, in Catalonia there has been no specific evaluation of women’s experiences regarding community sentences. The purpose of this article is to contribute to filling this gap by conducting qualitative research in Barcelona and Girona to analyse the experiences of women serving community sentences. To this end, 23 semi-structured interviews with women offenders are analysed. The results follow the trend found in research conducted in other jurisdictions and show that women have multiple issues, responsibilities and needs in comparison with men, and what works with female offenders is different from what works with male offenders with regard to supervision style, relationship with professionals and unpaid work or therapy environments. The findings make it possible to identify alternative responses that offer appropriate support and interventions to address women’s underlying problems and reduce reoffending. The article underscores the importance of listening to women’s voices in order to achieve a gender-sensitive criminal justice system.